Development of Stabilized Growth Factor-Loaded Hyaluronate– Collagen Dressing (HCD) matrix for impaired wound healing. Issue 1 (December 2016) - Choi, Seong; Ryu, Hyun; Lee, Kyoung-Mi; Kim, Hyun; Park, Ik; Cho, Wan; Shin, Hang-Cheol; Choi, Woo; Lee, Jin
Abstract Background Diabetes mellitus is a disease lack of insulin, which has severely delayed and impaired wound healing capacity. In the previous studies, various types of scaffolds and growth factors were used in impaired wound healing. However, there were several limitations to use them such as short half-life of growth factorsin vivo and inadequate experimental conditions of wound-dressing material. Thus, our study aimed to determine the biocompatibility and stability of the matrix containing structurally stabilized epidermal growth factor (S-EGF) and basic fibroblast growth factor (S-bFGF). Results and Discussion We stabilized EGF and bFGF that are structurally more stable than existing EGF and bFGF. We developed biocompatible matrix using S-EGF, S-bFGF, and hyaluronate– collagen dressing (HCD) matrix. The developed matrix, S-EGF and S-bFGF loaded on HCD matrix, had no cytotoxicity, in vitro . Also, these matrixes had longer releasing period that result in enhancement of half-life. Finally, when these matrixes were applied on the wound of diabetic mice, there were no inflammatory responses, in vivo . Thus, our results demonstrate that these matrixes are biologically safe and biocompatible as wound-dressing material. Conclusions Our stabilized EGF and bFGF was more stable than existing EGF and bFGF and the HCD matrix had the capacity to efficiently deliver growth factors. Thus, the S-EGF and S-bFGF loaded on HCD matrix had improved stability. Therefore, these matrixes may be suitable for impaired wound healing, resulting in application of clinical treatment.